ASEAN Developments in Merger Control. (March 2014) - Shiau, Daren; Chen, Elsa
Abstract: ASEAN nations have committed to establish competition policy and law by 2015, in accordance with the ASEAN Economic Community Blueprint (2007). Currently, five of the ten ASEAN member states have implemented generic competition laws, from which the three operative ASEAN merger control regimes are located (Indonesia, Singapore and Vietnam). As there is no overarching ASEAN merger control regime as found in the EU, this article seeks to highlight the unique issues which affect the implementation of competition policy in each ASEAN nation for the benefit of European competition law practitioners.